Conservation Easements and the “Term Creep” Problem (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
It has become apparent over the past several years that the decision to assign the label “easement” to conservation restrictions—designed to preserve and protect environmentally sensitive and productive agricultural lands, precious open space, and historically and architecturally significant lands and structures—has caused problems that most likely were not anticipated by those responsible for conceptualizing and popularizing this important and ubiquitous tool. Judges and commentators have wrestled with important questions concerning the application of common law concepts such as merger and cypres to the statutory creation we know as “conservation easements.”  There is also serious concern that other traditional principles and rules applicable to common law servitudes will make it more difficult for conservation easements to render their important service in perpetuity, given local and even global changes such as climate change and sea level rise. Conservation easements designed to protect critical habitat of protected species from development, to prevent the filling of wetlands, and to maintain longstanding agricultural use, for example, are vulnerable to such climate-related effects as shifts in habitat ranges, unprecedented coastal and inland flooding, dramatically altered growing patterns, saltwater intrusion, and supercharged tropical storms and hurricanes. Will there be any way to modify and thereby save these easements so that they can serve equally important (though technically different) public purposes?